Within session sequence of balance and plyometric exercises does not affect training adaptations with youth soccer athletes - Chaouachi, M.; Granacher, U.; Makhlouf, I.; Hammami, R.; Behm, D. G.; Chaouachi, A. (Journal of Sports Science & Medicine, 2017)
The integration of balance and plyometric training has been shown to provide significant improvements in sprint, jump, agility, and other performance measures in young athletes. It is not known if a specific within session balance and plyometric exercise sequence provides more effective training adaptations. The objective of the present study was to investigate the effects of using a sequence of alternating pairs of exercises versus a block (series) of all balance exercises followed by a block of plyometric exercises on components of physical fitness such as muscle strength, power, speed, agility, and balance. Twenty-six male adolescent soccer players (13.9 ± 0.3 years) participated in an 8-week training program that either alternated individual balance (e.g., exercises on unstable surfaces) and plyometric (e.g., jumps, hops, rebounds) exercises or performed a block of balance exercises prior to a block of plyometric exercises within each training session. Pre- and post-training measures included proxies of strength, power, agility, sprint, and balance such as countermovement jumps, isometric back and knee extension strength, standing long jump, 10 and 30-m sprints, agility, standing stork, and Y-balance tests. Both groups exhibited significant, generally large magnitude (effect sizes) training improvements for all measures with mean performance increases of approximately >30%. There were no significant differences between the training groups over time. The results demonstrate the effectiveness of combining balance and plyometric exercises within a training session on components of physical fitness with young adolescents. The improved performance outcomes were not significantly influenced by the within session exercise sequence